Increased risk of graft failure and mortality in Dutch recipients receiving an expanded criteria donor kidney transplant. (January 2017) - van Ittersum, Frans J.; Hemke, Aline C.; Dekker, Friedo W.; Hilbrands, Luuk B.; Christiaans, Maarten H. L.; Roodnat, Joke I.; Hoitsma, Andries J.; van Diepen, Merel
Summary: Survival of expanded criteria donor (ECD) kidneys and their recipients has not been thoroughly evaluated in Europe. Therefore, we compared the outcome of ECD and non‐ECD kidney transplantations in a Dutch cohort, stratifying by age and diabetes. In all first Dutch kidney transplants in recipients ≥18 years between 1995 and 2005, both relative risks (hazard ratios, HR) and adjusted absolute risk differences (RD) for ECD kidney transplantation were analysed. In 3062 transplantations [recipient age 49.0 (12.8) years; 20% ECD], ECD kidney transplantation was associated with graft failure including death [HR 1.62 (1.44–1.82)]. The adjusted HR was lower in recipients ≥60 years of age [1.32 (1.07–1.63)] than in recipients 40–59 years [1.71 (1.44–2.02) P = 0.12 for comparison with ≥60 years] and recipients 18–39 years [1.92 (1.42–2.62) P = 0.03 for comparison with ≥60 years]. RDs showed a similar pattern. In diabetics, the risks for graft failure and death were higher than in the nondiabetics. ECD kidney grafts have a poorer prognosis than non‐ECD grafts, especially in younger recipients (<60 years), and diabetic recipients. Further studies and ethical discussions should reveal whether ECD kidneys should preferentially be allocated to specific subgroups, such as elderly and nondiabetic individuals.